Modafinil effects on reinstatement of methamphetamine-seeking in a rat model of relapse - Reichel, Carmela M. (2010)
RATIONALE: Modafinil (Provigil) is a wake-promoting drug characterized by cognitive enhancing abilities. Recent clinical data have supported the use of modafinil for treatment of chronic psychostimulant addiction and relapse prevention. MATERIALS AND METHODS: We used an intravenous methamphetamine (meth) self-administration procedure to assess the dose-dependent effects of modafinil on reinstatement following abstinence and after extinction on conditioned-cue and meth-primed reinstatement of meth-seeking. RESULTS: Modafinil attenuated active lever responding in multiple reinstatement conditions – context-induced, conditioned cue, and meth-prime. The most pronounced and consistent effect was on meth-primed reinstatement, and modafinil did not reinstate meth-seeking when tested alone. DISCUSSION: These findings support clinical findings in humans that modafinil may be an effective therapeutic agent for the prevention of relapse in abstinent meth users.